Answer:
Step-by-step explanation:
In exponent multiplication, if base are same just add the powers.


By applying the concept of the inverse of a function and <em>algebraic</em> handling, we conclude that the inverse of f(x) = (- 2 · x + 2)/(x + 7) is g(x) = (- 7 · x + 2)/(x + 2).
<h3>How to find the inverse of a function</h3>
In this question we have a <em>rational</em> function f(x) and finding its inverse consists in clearing x in terms of f(x). Prior any algebraic handling, we need to apply the following substitutions:



x · (y + 7) = - 2 · y + 2
x · y + 7 · x = - 2 · y + 2
2 · y + x · y = - 7 · x + 2
y · (2 + x) = - 7 · x + 2

By applying the concept of the inverse of a function and <em>algebraic</em> handling, we conclude that the inverse of f(x) = (- 2 · x + 2)/(x + 7) is g(x) = (- 7 · x + 2)/(x + 2).
To learn more on inverses: brainly.com/question/7181576
#SPJ1
Answer:
9 minutes
Step-by-step explanation:
60=15+5t
45=5t : subtract 15 from both sides
9=t : divide by 5 for both side
Answer:
<em>5x-y=9, y=5x+19 write both equations in same formy=5x-9 for the first and havey=5x+19 for the second. These are two parallel lines with different intercepts. They do not intersect or coincide. No </em><em>solutions</em>
<em> </em>
<em>and y=6x+14, 12x-2y=-28 write both equations in same formy=6x+142y=12x+28 or y=6x+14. They are the same line. The solution is all of the points on the line.</em>
Step-by-step explanation:
<em>I </em><em>hope</em><em> it</em><em> will</em><em> help</em><em> you</em><em> have</em><em> a</em><em> great</em><em> day</em><em> bye</em><em> and</em><em> Mark</em><em> brainlist</em><em> if</em><em> the</em><em> answer</em><em> is</em><em> correct</em><em> </em><em>I </em><em>am </em><em>sorry</em><em> </em><em>if </em><em>the </em><em>answer</em><em> is</em><em> </em><em>worng</em><em> </em>
<em>
</em>
<em>#</em><em>c</em><em>a</em><em>r</em><em>r</em><em>y</em><em> </em><em>on </em><em>learning</em>